Self-translation as re-creation: The incipit of a fantasy novel in French (original language) and English - Emma SCHÜTZ (E-REA)
The following is a creative translation in English of the first chapter of a novel I completed in 2021 and which is due to be published by BeetleBooks Publishing in 2023. Translating the novel would form the core of the Ph.D. I hope to write as a doctoral student in ‘Pratiques et théories de la création littéraire et artistique’ at Aix-Marseille University.It is my project to translate this choral novel, the first volume of Sublimes, and thus rewrite it benefiting from the freedom afforded by self-translation, within the framework provided by the doctoral school or as an autonomous work.The trilogy, entitled Sublimes in French and English, shows two parallel worlds: Earth in 2082, a rather dystopian take on our near future, and Arcadia, a fantasy world where magic once reigned but has long since disappeared. The only surviving supernatural species are the Sublime, beautiful and ageless (yet mortal) people, who look human… and are anything but, as they routinely consume human flesh.The first chapter follows Pascal, an Earthling and a student at a university destined for the elite. After waking up in an alien landscape with no memory of his arrival, Pascal discovers that he is not alone: with him are five other Academy students, as well as Yolanda, a gardener at the university. As the group is greeted by a dozen old-fashioned soldiers, they understand, a little late, that their fate is sealed: they are prey and, if they cannot escape, will become food.The novel moves forward with each chapter presenting the point of view of a different character, and no omniscient narrator. Each “voice” is associated with a different style and language.The translation of the first chapter allowed for creation, as I had hoped and suspected: some things are easier described in French or English and my style was not the easiest to harness in English, as I have written very little fiction in English compared to French (my mother tongue).However, there have been a few surprising discoveries! For example, I struggled with writing dialogues in French, whereas they almost flowed in English. On the other hand, working with such attention to detail revealed a few overlooked repetitions in the French text, although it had been read, reread and corrected by myself and many others. I therefore cannot wait to pursue this endeavour and unearth the many joys – and certainly, the many more challenges – of the re-creation that lies in self-translation.